Terorisme di Indonesia : Pemufakatan Jahat Dalam Tindak Pidana Terorisme studi Putusan Nomor 351_PIDSUS_2017_PN JktTim - Fadhil Sadam Rusbal; Taun Taun (Fakultas Hukum Universitas PGRI Palangkaraya, 2023)
Acts of terrorism in Indonesia often stem from the gathering of a religious study that has been signaled with the doctrine of radical terrorism that has been smuggled by irresponsible people or also people who have joined a global terrorism group known as ISIS, In launching acts of terrorism, one way is to detonate an explosive device in the form of a bomb or other explosive device aimed at either a place of worship or directly aimed at an individual who is not Muslim, In the implementation of this act of terrorism itself can be carried out either alone or in a group by conspiring with each other to do the terrorism act. This article aims to understand the elements of another criminal offense, namely criminal conspiracy, which is one of the bases for the crime of terrorism, as seen from the study of the decision of the East Jakarta District Court Number 351/Pid.Sus/2017/PN. Jkt.Tim. The type of research in this article is normative legal research, using a qualitative analysis method in understanding the fulfillment of the elements of the offense of criminal conspiracy in the crime of terrorism based on the East Jakarta District Court Decision. The results of the analysis found that if the defendant in the relevant decision has been proven to have fulfilled each element of criminal conspiracy in the crime of terrorism, therefore it can be stated that the perpetrators of the crime of terrorism often carry out criminal conspiracy before committing crime of terrorism.